Statistika dalam Manajemen Pendidikan Islam: Pengambilan Keputusan Berbasis Data untuk Meningkatkan Mutu Pendidikan - Prihaten Maskhuliah; Duwi Lasmiyati; Siti Aisa Alis; Arsyad S. Tupong (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Decision-making is a fundamental component of Islamic educational management that significantly influences the quality and effectiveness of educational institutions. Sound decisions should be supported by accurate, reliable, and evidence-based information. Therefore, statistical methods play an essential role in collecting, processing, analyzing, and interpreting educational data to produce meaningful information for policy formulation. This article aims to examine the role of educational statistics in Islamic educational management, particularly in supporting data-driven decision-making to enhance educational quality. The study employed a literature review method by analyzing books, journal articles, and other relevant scientific publications related to educational management and statistical applications. The findings indicate that effective data management enables educational leaders to identify institutional challenges, evaluate program performance, allocate resources efficiently, and formulate strategic policies based on empirical evidence. Furthermore, the application of statistics contributes to improving transparency, accountability, and continuous quality improvement within Islamic educational institutions. Consequently, statistics should not only be regarded as a technical tool for data analysis but also as a strategic instrument that supports informed decision-making and sustainable educational development. The integration of statistical approaches into educational management can strengthen institutional governance and improve educational outcomes in Islamic educational settings.